Pengaruh Kompensasi dan Lingkungan Kerja terhadap Komitmen Organisasi serta Implikasinya pada Kinerja Pegawai Puskesmas Talang Pangeran Kabupaten Ogan Ilir - Febrianto, Herli (Forum Bisnis Kewirausahaan, 2024)
This study aims to determine the effect of compensation and work environment on organizational commitment and its implications on employee performance. The population in the study was 52 employees. The sample technique used is a saturated sample. This study used SEM analysis. The results of this study show that there is a significant influence of compensation and work environment on organizational commitment, there is a significant influence of compensation and work environment on employee performance and there is a significant influence of organizational commitment on employee performance.